Dietary Intervention and Supplements in the Management of Psoriasis: Current Perspectives - Chung M; Bartholomew E; Yeroushalmi S; Hakimi M; Bhutani T; Liao W (Dove Medical Press, 2022)
Mimi Chung, Erin Bartholomew, Samuel Yeroushalmi, Marwa Hakimi, Tina Bhutani, Wilson Liao The University of California, San Francisco, Department of Dermatology, San Francisco, CA, USACorrespondence: Mimi Chung, 515 Spruce Street, San Francisco, CA, 94118, USA, Tel +415-944-7618, Email mimi.chung244@gmail.comAbstract: Nutrition is a complex topic encompassing diet and a variety of supplements including vitamins, fish oil, herbal products, and probiotics. Patients with psoriasis display high interest in understanding the potential impact of nutritional modifications on their psoriasis. In this review, we examine the evidence for nutritional interventions in psoriasis and summarize important concepts. We found that certain diets, such as low-calorie diets for obese patients, gluten-free diets for patients with comorbid celiac disease, and the Mediterranean diet, may have benefits for psoriasis patients. Supplements in general do not show strong evidence of benefit, though more studies are required given the heterogeneity of these trials. Finally, the gut microbiome has drawn considerable interest in recent years, with specific probiotics showing promising results for psoriasis patients and warranting further exploration.Keywords: nutrition, supplements, probiotics, inflammatory skin disease